The cabinet member as policy entrepreneur - Thompson Carolyn Rinkus
The role of cabinet member as policy entrepeneur has received little attention in the literature of political science and public administration. Cabnet members have no formal authority or constitutional mandate. Additionally, their identification with particular agency missions has subjected cabinet secretaries to the suspicion of "going native", thus further diminishing their capacity for policy initiation. Presidential concern with controlling the executive branch perhaps reached its peak during the Reagan administration, when virtually all political appointments and policy decisions were controlled within the office of the president. This research examines the role of Cabinet Secretary Otis R. Bowen, MD
Keywords: Political Science -- U.S.A.; Public Administration -- U.S.A.